Assessing strategic knowledge assets in e-business. (2nd November 2004) - Marr, Bernard; Schiuma, Giovanni; Neely, Andy
Capabilities and their underlying knowledge assets represent a major competitive resource for knowledge-intensive organisations such as e-businesses. The research presented in this paper utilises a series of case studies to identify the key knowledge assets for e-businesses. The paper suggests the Knowledge Assets Map as a framework to identify and manage key capabilities and key assets in today¡¦s economy. The Knowledge Asset Map identifies the following six areas as critical stakeholder relationships, human resources, physical infrastructure, culture, practices and routines, and intellectual property. Furthermore, the paper provides managerial guidelines to design knowledge assets metrics.